2021
DOI: 10.1016/j.amsu.2021.102254
|View full text |Cite
|
Sign up to set email alerts
|

Combination of platelet rich plasma and stromal vascular fraction on the level of vascular endothelial growth factor in rat subjects experiencing deep dermal burn injury

Abstract: Background The healing process of burns includes coagulation, inflammation, and remodeling. Vascular endothelial growth factor (VEGF) is involved throughout this healing process. Stem cells from the platelet-rich plasma (PRP) with stromal vascular fraction (SVF) can increase concentrations of growth factors, including VEGF. This is expected to accelerate burn healing. The aim of this study was to determine the effect of a combination of PRP and SVF on VEGF levels in a rats model of deep dermal bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Protein levels of NF-kβ and TNF-α were detected by MPO Sandwich ELISA with Catalog No. Ls-F12149 and LSF12798 were purchased from Life Span Bio Sciences, Inc. (Seattle, USA) according to the manufacturer's instructions [ [21] , [22] , [23] , [24] ].…”
Section: Methodsmentioning
confidence: 99%
“…Protein levels of NF-kβ and TNF-α were detected by MPO Sandwich ELISA with Catalog No. Ls-F12149 and LSF12798 were purchased from Life Span Bio Sciences, Inc. (Seattle, USA) according to the manufacturer's instructions [ [21] , [22] , [23] , [24] ].…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] Platelet Rich Plasma (PRP) is known to play an important role in burn healing, mainly due to the many growth factors it contains. [14][15][16] Platelet-derived endothelial cell growth factor (PDGF) and insulin-like growth factor-I (IGF-I) are examples of growth factors that are present in PRP, inhibit the apoptotic pathway during cell turnover and facilitate different stages of wound healing. Both SVFs and PRP have the ability to accelerate epithelialization, induce angiogenesis, and stimulate fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…This study is a continuation of the previous studies. 10,16,17 The results obtained from the previous studies which compared the local injection of SVFs, PRP, the combination of SVFs and PRP, and Vaseline (positive control) found that the combination of SVFs and PRP showed a better epithelialization result (complete closure on day 10) compared to SVFs group, PRP group, or Vaseline group alone. In addition, the formation of collagen was thicker, and the number of fibroblasts were higher in the combination group.…”
Section: Introductionmentioning
confidence: 99%
“…The cage was standard-shaped, cleaned regularly, and given lighting (12 h light/dark photoperiod) [ 28 , 29 ]. The laboratory animals were treated according to National Institutes of Health guidelines, and this work was carried out in line with the ARRIVE Guidelines for Reporting Animal Research [ [30] , [31] , [32] ].…”
Section: Methodsmentioning
confidence: 99%